TAXING DIGITAL ADVERTISING: A PROPOSAL TO INDONESIA - Ardin, Galih (Direktorat Jenderal Pajak, 2021)
Tax on digital economy activities has become a widely discussed issue in the world because of the limitation on the permanent establishment concept in anticipating the digital economy's externalities. The failure of OECD countries to reach digital economic taxation agreements also caused these countries to take unilateral measures in securing their respective interests. Indonesia, as a country with considerable digital economy value in the Southeast Asia region, plans to implement the significant economic presence concept to secure its tax revenue that cannot be captured by PE concept in the digital cross-border transaction. However, the implementation of this new nexus could generate new challenges in the Indonesia taxation system. This study seeks to provide alternatives to the Indonesian government regarding the taxable presence and taxation methods on the digital economy, especially digital advertising, by conducting examination and evaluation through current nexuses, the international proposals, and other countries' experience in addressing tax challenges in the digital advertising.